Analisis Manajemen Pembangkit Listrik Mikrohidro (PLTMH) Kabupaten Puncak Papua Tengah - Wonda, Rony Jik; Priyambodo, Bambang (Universitas Batanghari Jambi, 2024)
Micro hydro power plants (PLTMH) are small-scale power plants that are generally built in places that are not touched by the electricity network but the area has sufficient water potential to generate electrical energy. The Puncak Regency of Central Papua is surrounded by mountains and valleys. The only way of transportation is the air route. The condition of Puncak district is also known as a conflict-prone area, so road access is not yet connected between regencies, so currently in and out using the air way. The existing PLTMH can be managed properly so that the community and district government can carry out their activities as usual. For the sake of the progress of the beloved Puncak Regency, it is one of the responsibilities for the community, the government, community leaders and security to take care of it together so that the area we love can progress.